Occupy heaven: are God, religion, and politics beyond rescue? - Rieger, Joerg (Resistance and visions, 2014)
Religion today presents itself mostly as a conservative phenomenon. Too often in history religion put itself on the side of the status quo. As a result, it may seem as if God, religion, and politics are indeed beyond rescue. This essay seeks to introduce alternative models, beginning with the realization that progressive forms of religion were part of significant transformations in history. Recent experiences with the Occupy Wall Street movement reflect many of these progressive characteristics, particularly the relation of progressive politics, economics, and religion. The critique that emerges from these experiences is not merely directed at dominant power, expressed today in politics and economics, but also at dominant power as it is embodied by religion. Such critique points to lived alternatives in which power does not flow from the top down but from the bottom up. These alternative experiences of religion and power throw new light on many Jewish and Christian traditions, which embody power in a different way. Not only could these traditions never be controlled completely by the prevailing empires, they also produced alternative embodiments of power, linked to alternative images of God. The result is a new understanding of solidarity, which has the potential to bring together the streams of the various liberation movements without neglecting differences and tensions. Based on this new solidarity, entrenched images of immanence and transcendence can be reconstructed, producing new visions of God, religion, and politics.